Pendidikan Multikultural Dalam Islam: Toleransi Beragama dalam Kehidupan Masyarakat - Siddeh, Khoirul Anam; Bakri, Maskuri (el Buhuth: Borneo Journal of Islamic Studies, 2021)
Tolerance (tasamuh) is one of the core teachings of Islam which is very urgent to continue to be developed and built in a multicultural society. With tolerance we can appreciate and accept differences with others. So that everything goes according to nature, peacefully, without any coercion and threats from other parties. History records that Muslims have a very high tolerance, starting from the period of the Prophet, the period of the Companions, and subsequent generations. In Indonesia, Muslims have very good tolerance for followers of other religions, so they can live side by side in peace. But on the other hand, recently there have been various conflicts that have led to violence between religious communities. Seeing this phenomenon, it is necessary for the cooperation of all parties to initiate, seek, and realize tolerance in the daily life of this nation's multicultural society. So that the ideals of the formation of a civil society, namely a society that is inclusive, tolerant, humanist, and egalitarian, is actually achieved and is a reality.